China in the backyard: Chinese assertiveness and United States\' hegemony in Latin America between 2001 and 2015 - Urdinez, Francisco (2017)
This thesis seeks to analyse the relationship between China\'s assertiveness and US hegemony in Latin America in the period 2001-2015. The analysis was done by mixing quantitative and qualitative methods, and has as a central hypothesis that the American hegemony (which is assumed in retraction) negatively affected China\'s assertiveness in the region. The thesis consists of seven chapters, ranging from general conclusions to particular conclusions. The hypothesis proves empirically, but variations are also found between countries and variations by economic activity. I conclude that China approached Latin America through a strategy of accommodative assertiveness, and Latin American countries responded to that approach aiming at diversifying their relationships.